Biohydrogen and poly-β-hydroxybutyrate production by winery wastewater photofermentation: Effect of substrate concentration and nitrogen source. (1st October 2020) - Policastro, Grazia; Luongo, Vincenzo; Fabbricino, Massimiliano
Abstract: The applicability and convenience of biohydrogen and poly-β-hydroxybutyrate production through single-stage photofermentation of winery wastewater is demonstrated in the present study. Experiments are conducted using a purple non-sulfur bacteria mixed consortium, subject to variable nutrient conditions, to analyze the effect of initial chemical oxygen demand and the available nitrogen source on the metabolic response. Results show that winery wastewater is a promising substrate for photofermentation processes, despite the presence of inhibiting compounds such as phenolics. Nonetheless, the initial chemical oxygen demand must be carefully controlled to maximize hydrogen production. Up to 468 mL L −1 of hydrogen and 203 mg L −1 of poly-β-hydroxybutyrate can be produced starting from an initial chemical oxygen demand of 1500 mg L −1 . The used nitrogen source may direct substrate transformation through different metabolic pathways. Interestingly, the maximum production of both hydrogen and poly-β-hydroxybutyrate occurred when glutamate was used as the nitrogen source. Highlights: Photofermentation of winery wastewater allows contextual H2 and PHB production. Use of mixed PNSB cultures is beneficial to contrast the effect of toxic compounds. Nitrogen source affects photofermentation development pathway. N-Glutamate enhances both H2 production and PHB concentration. Inorganic nitrogen enhances PHB accumulation by PNSB.